Narcissism and the Pleasures of Extinction: For the Centenary of "Beyond the Pleasure Principle" - Dany Nobus (EJP import test, 2021)
Summary: Taking advantage of the hundredth anniversary of the first publication of Freud’s controversial essay ‘Beyond the Pleasure Principle’, this paper questions why this seminal text has proven so difficult to read and examines its enduring significance for the contemporary state of the human condition. It is demonstrated that the key paradox pervading Freud’s essay is not that there is a death drive which operates beyond the pleasure principle, but that it is the libidinal investment of the ego, in the form of narcissism, which drives the human life form towards its own extinction. It is argued that the more a living organism is narcissistically invested in protecting its own existence, the more it is at risk of unwittingly facilitating and expediting its annihilation, because auto-sexual investment does not contribute to solid community building, creative cross-fertilisation and progressive revitalisation. Even though this first, biogenetic axis of Freud’s ontogenetic theory is extended with an equally controversial, anthropogenetic axis in Moses and Monotheism, the first axis is already routinely rejected owing to its traumatic impact on the reader’s own narcissism. This process of repression and displacement of Freud’s message is equally, and perhaps even more at work during these unprecedented times of a global, human-made pandemic, because narcissism may be more prevalent now than it was one hundred years ago, driven by the accumulative economic conditions of global capitalism. Nam Sibyllam quidem Cumis ego ipse oculis meis vidi in ampulla pendere, et cum illi pueri dicerent: Σίβυλλα τί θέλεις; respondebat illa: ἀποθανεῖν θέλω. Petronius, Satyricon, 48
Keywords: Death Drive; extinction; Narcissism; Pleasure principle